(untitled) (REVISTA NODO, 2022)
The design of urban projects has had an important boom not only due to the identification of the city from its forms, but also as the set of functional elements that integrate it and make up its essence. The purpose of this work is to expose macro indicators for the appreciation of public recreational spaces, as well as connectivity conditions of them. There are presented inclusion and belonging categories to measure those attributes in the user population, from which ten quantitative macro indicators emerge, which in turn give rise to 180 sub indicators, in addition to the model for a global indicator. The contributions of this study are reflected in the differentiation that these categories have with respect to studies of an urban design nature to intervene in the management and planning of policies that respond to the guidelines of the right to the city.